2021
DOI: 10.46754/jssm.2021.07.016
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Value of Ecosystem Services of Rubber-Based Agroforest Plantations in South Thailand

Abstract: The objective of this study was to estimate the ecosystem service values of three types of rubber-based agroforest plantations and monoculture rubber plantations in the southern region of Thailand, covering a life cycle of 25 years. Three ecosystem services were investigated in this study: timber production, CO 2 sequestration, and O 2 production. The study used data collected from 29 plantations and used growth prediction models from previous research to determine the quantity and value of the ecosystem servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Although there is no research on the sago palm value of CO2 sequestration to compare with this study, there is work done on other commercial crops. Compared with rubber monocultures in the year 25 of planting, sago palm has a higher value of CO2 sequestration from living biomass, which was 581.23 USD, compared to 565.8 USD for rubber monocultures [37]. Furthermore, in year 26 of planting, sago palm plantations continue to provide CO2 sequestration value, while rubber monoculture requires replanting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no research on the sago palm value of CO2 sequestration to compare with this study, there is work done on other commercial crops. Compared with rubber monocultures in the year 25 of planting, sago palm has a higher value of CO2 sequestration from living biomass, which was 581.23 USD, compared to 565.8 USD for rubber monocultures [37]. Furthermore, in year 26 of planting, sago palm plantations continue to provide CO2 sequestration value, while rubber monoculture requires replanting.…”
Section: Resultsmentioning
confidence: 99%
“…This replanting process results in biomass carbon loss from the wood harvesting process, which affects the soil's accumulated organic carbon during the harvested year [38]. However, the wood product of rubber trees is considered a provisioning service (products obtained from ecosystems including food, materials, fiber, fuel, and genetic resources [13]) that can provide direct income for farmers in the year 25 [37] and may affect the net present value of the direct benefit. The need to study the cost-benefit of both direct and indirect income covering the replanting year is evident in order to compare the highest benefit of each commercial crop planting more clearly.…”
Section: Resultsmentioning
confidence: 99%
“…Suarez and W. Gwozdz (Meylan et al, 2017), rice (Liu et al, 2020), and umari (Wood et al, 2016); improvements in carbon stock in topsoil was reported by palm oil (Labrière et al, 2015). Moreover, climatic regulation, air purification, oxygen generation and CO 2 sequestration were reported in palm oil, rubber plantations and rice (Lavelle et al, 2014;Liu et al, 2020;Nattharom et al, 2021;Zhang et al, 2012). Other positive contributions of monocultures were net primary production in grain (Li et al, 2020), and contributions for pollination by coffee (De Beenhouwer et al, 2013), or even maintenance of bats species richness in palm oil plantations (Celygómez et al, 2021).…”
Section: Es From Monocultures: Synergiesmentioning
confidence: 99%